FINANCIAL RATIO ANALYSIS IN PREDICTING PROFIT CHANGES IN INDUSTRIAL COMPANIES CONSUMPTION GOODS LISTED ON THE EXCHANGE INDONESIAN EFFECTS 2019-2022 - Endang Ratnawati zai; Bottor Renata Amanda Sirait; Jessi Charina Sembiring; Dewi Simatupang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Financial reports are an important piece of information that contains various conditions of the company in a certain period, and can be a general picture in measuring the company's success, especially from the perspective of investors in order to predict changes in company profits in the future. This research aims to analyze financial report data of consumer goods companies listed on the Indonesia Stock Exchange (BEI) in the period 2019 to 2022 to determine the effect of financial ratios including Liquidity, Profitability, Solvency and Activity on Profit Changes with a total of 56 samples. Based on the research results, it shows that the Liquidity Ratio through the Current Ratio (CR) proxy and the Solvency Ratio through the Debt to Assets Ratio (DAR) have a negative effect on Profit Changes in consumer goods companies. Meanwhile, the Profitability Ratio through Return on Assets (ROA) and the Activity Ratio with Total Assets Turnover (TAT) show a significantly positive effect on Profit Changes in consumer goods companies.